VD_FINDINFO HC / 2012 / 664 vom 23. Oktober 2012 - VD Tribunal cantonal (2012)
EXPULSION DE LOCATAIRE, DEMEURE DU DÉBITEUR, PROCÉDURE SOMMAIRE, RÉSILIATION, EFFICACITÉ | 257d CO, 257 CPC (CH), 308 al. 1 let. a CPC (CH), 308 al. 2 CPC (CH), 318 al. 1 CPC (CH)